2017
DOI: 10.3122/jabfm.2017.04.170046
|View full text |Cite
|
Sign up to set email alerts
|

Developing Electronic Health Record (EHR) Strategies Related to Health Center Patients' Social Determinants of Health

Abstract: Background These ‘Social determinants of heath’ (SDH) are non-clinical factors that profoundly impact health. Helping community health centers (CHCs) document patients’ SDH data in electronic health records (EHRs) could yield substantial health benefits, but little has been reported about CHCs’ development of EHR-based tools for SDH data collection and presentation. Methods We worked with 27 diverse CHC stakeholders to develop strategies for optimizing SDH data collection and presentation in their EHR, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
153
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(159 citation statements)
references
References 42 publications
5
153
0
1
Order By: Relevance
“…Recent research has suggested that exactly this approach—limiting screening to only a subset of patients and using information in electronic medical records to target this subset—should be given consideration as a potential strategy for minimizing the workload burden placed on health care teams when administering screenings for social determinants of health . In the aggregate, this approach would greatly reduce the amount of clinician time dedicated to the HSCR given the size of the VHA patient population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent research has suggested that exactly this approach—limiting screening to only a subset of patients and using information in electronic medical records to target this subset—should be given consideration as a potential strategy for minimizing the workload burden placed on health care teams when administering screenings for social determinants of health . In the aggregate, this approach would greatly reduce the amount of clinician time dedicated to the HSCR given the size of the VHA patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have documented the challenges of effectively using information from self-reported screening instruments on social determinants of health such as housing instability. [20][21][22][23][24] These challenges fall into two broad categories: (a) determining how to resolve the logistical, resource, and workload issues associated with the collection of information about housing instability and other social factors from patients; and (b) optimizing procedures for taking action on such information. With respect to the first set of challenges, evidence suggests that workload concerns are barriers to the effective implementation of screening tools.…”
Section: Byrne Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…42 Others have outlined the specific questions and processes that should be used to standardize collection of individual social needs in primary care settings. 43 At a system level, organizations are experimenting with novel methods for addressing social needs. CommunityRx combines e-prescribing and community engagement to connect patients with community resources, via the diagnoses generated in EHRs.…”
Section: Discussionmentioning
confidence: 99%